Critical Thinking di Era Distorsi Informasi: Membedah Hoaks, Misinformasi, dan Bias Kognitif pada Generasi Z - Dinda Ananda Nasution; M. Chaerul Rizky; Febri Ayu Anggraeini; Farhan Yunanda Surbakti; Dion Alfa Harefa; Fahrul Ramadan (Universitas Veteran Bangun Nusantara, 2025)
The rapid development of digital media has created a complex information ecosystem, where data flows massively without adequate quality filters and verification. This condition increases the potential for information distortion, including hoaxes, misinformation, and cognitive bias that significantly affect the information behavior of society. Generation Z as digital natives becomes the most vulnerable group due to high exposure to social media and algorithms that personalize content. This research aims to analyze the critical thinking ability of Generation Z in facing information distortion, identify cognitive and structural factors that influence vulnerability to hoaxes, and formulate strategies for strengthening digital literacy based on modern pedagogical approaches. This research uses a systematic literature study method by integrating empirical findings from academic papers, national journals indexed by Sinta, and accredited international journals. The results of the research show that although Generation Z has high technological ability, their critical thinking ability is not evenly distributed, especially in aspects of source verification, evidence analysis, and awareness of cognitive bias. Educational interventions such as Problem-Based Learning, critical digital literacy, training to distinguish fact-opinion-hoax, and guided inquiry-based learning have proven effective in increasing information resilience. This research produces a conceptual model for strengthening critical thinking as the foundation of 21st-century digital literacy.